Measuring the level of awareness for sustainable development in rural construction (Case Study: Guilan Architecture) - Mehran Mehrdoust Shahrestani; Ali Asgharzadeh; Hamzeh Golamalizadeh (تحقیقات کاربردی علوم جغرافیایی)
The main goal of sustainable development in the village are use to social, economic and environmental resources and capacities. Awareness for sustainable development is a subject that has been less discussed. Accordingly, rural assets and funds can be the basis for achieving the goals of sustainable rural development. The purpose of this paper is to measure awareness for sustainable development in rural construction in Guilan province. This research is developmental and surveying. In this study, which was done by the architects of Guilan Construction Engineering Organization, the data collection method was used to answer the research questions, using both documentary (secondary data) and survey (primary data) and Questionnaire with Likert spectrum. Using Cronbach's alpha formula in SPSS software, the reliability of different parts of the research questionnaire was 0.802 to 0.816.